Revisiting γ-alumina surface models through the topotactic transformation of boehmite surfaces - Pigeon, Thomas; Chizallet, Céline; Raybaud, Pascal (Journal of catalysis, 2022)
[Display omitted] •Impact of the topotactic transformation applied to surface models.•16 γ-alumina surface models are identified by DFT calculations.•(110) basal and (110) lateral surfaces exhibit distinct Brønsted and Lewis sites.•Quantitative comparison of surface energies as a function of T and PH2O.•Mapping of the evolution of concentrations and types of Brønsted sites. The rational understanding of γ-alumina (γ-Al2O3) supported catalysts requires an ever more improved atomic scale determination of the support’s surface properties. By using density functional theory (DFT) calculations, we show how the structural and energetic surface properties of alumina crystallites intrinsically depend on its synthesis pathway. Considering the case study of the topotactic transformation of boehmite (γ-AlOOH) into γ-Al2O3 taking place during calcination, we propose a methodology to mimic this pathway by reconstructing relevant slabs of boehmite into γ-alumina slabs following 3 steps: dehydration, contraction/translation and Al migration into spinel or non-spinel sites. On the one hand, we confirm the reliability of some earlier 100, 110 and 111 surface structures determined by standard bulk cleavage approach. Moreover, we find new γ-alumina surfaces harboring Brønsted acid sites (BAS) and Lewis acid sites (LAS) with specific local structures. More strikingly, we find that the basal 110b surface of alumina inherited from the (010) basal surface of boehmite, exhibits a larger number of isolated µ2-OH groups than the lateral 110l surface. For the lateral 110l (respectively 111) orientation, four (respectively three) thermodynamically competing surfaces are identified, including models earlier proposed. These results are induced by finite size and morphology effects during the topotactic transformation of boehmite crystallites. Thanks to a thorough comparative analysis of morphology and nature of BAS and LAS as a function of thermal treatment and water pressure for each surface, we identify coherent chemical families of surfaces across the main crystallographic orientations. These features open the door to a better differentiation of the reactivity of the basal alumina surfaces from the lateral ones.